1991
DOI: 10.3133/pp1512
|View full text |Cite
|
Sign up to set email alerts
|

Description and development of the Cordilleran orogenic belt in the Southwestern United States and northern Mexico

Abstract: The Cordilleran erogenic belt forms a continuous zone of compressive deformation of Late Jurassic to Eocene age resulting from collision of the converging North American plate with northeast Pacific plates. The segment of the belt between El Paso, Texas, and Las Vegas, Nevada, differs from adjacent segments in that subordinate tectonic zones are truncated along an unusual kind of frontal zone. This difference is believed to result from a combination of oblique collision of the deformation zones with the semicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…En adición a estos datos, en el Sistema Cordillerano (Orogenia Nevadiana) existen efectos tectónicos asociados al movimiento de placas del oeste de Norteamérica y también se reconoce una discordancia regional en el Berriasiano (Drewes, 1991). En este entorno geodinámico existe la disyuntiva para resolver cuál evento tuvo mayor influencia en el noreste de México; tal parece que el cambio relativo del nivel del mar predomina sobre la tectónica.…”
Section: Consideracionesunclassified
“…En adición a estos datos, en el Sistema Cordillerano (Orogenia Nevadiana) existen efectos tectónicos asociados al movimiento de placas del oeste de Norteamérica y también se reconoce una discordancia regional en el Berriasiano (Drewes, 1991). En este entorno geodinámico existe la disyuntiva para resolver cuál evento tuvo mayor influencia en el noreste de México; tal parece que el cambio relativo del nivel del mar predomina sobre la tectónica.…”
Section: Consideracionesunclassified
“…Uphoff's interpretation is that the Cuchillo Formation (Aptian-Albian) is the oldest Mesozoic unit that is continuous across the "Clint fault" and he suggested that pre-Cuchillo Mesozoic activity along the fault removed any Jurassic rocks that were present to the north of the fault. Figure 15 shows an alternative interpretation to that shown by Uphoff (1978) and Drewes (1991a). Here the "Clint fault" is interpreted as a part of the Texas Lineament and is interpreted as a Jurassic basin-bounding fault that was reactivated during the Laramide orogeny as a reverse fault and again during Tertiary time as a normal fault; Paleozoic faulting along the Clint fault zone is possible but not necessary.…”
Section: Meters K C U K Bmentioning
confidence: 99%
“…Depth of the section, in 2-way travel time is 4 seconds (fair to good reflectors to about 3 seconds), which corresponds to depths of 10 to 12 km (estimated from velocity data from a refraction survey reported by Tovar-R. et. al., 1978, p. 111) and should show thrust faulting at or above the maximum depth of sole thrusts (about 5 km) postulated by Corbitt (1988) and Drewes (1991a). Figure 30) also showed a reflection seismic line through PEMEX (MOY-1), and several lines (Figures 14 and 29) in the vicinity of PEMEX Banco Lucero-1 (BL-1) that do not show thrust faults.…”
Section: Northwestern Areamentioning
confidence: 99%
See 2 more Smart Citations